Strategi Pendidikan Karakter: Membentuk Etika dan Nilai pada Generasi Muda Studi di SD Negeri 02 Amban Monokwari - Songbes, Anna Maria Hilda; Sutrisno, Sutrisno; Indiati, Indiati (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to find out the strategy of character education in shaping ethics and values in the younger generation studying at SD Negeri 02 Amban Monokwari. The type of research used in this study is a literature review method using a qualitative approach. The main source of data for this research is research articles that have been published in various scientific journals and indexed on the google scholar database. Other sources of supporting data are books and other documents relevant to the focus of the research. The data analysis technique used is qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The results of data analysis show that the development of the personality of the younger generation in modern society is a challenge because of the interaction of influences from various factors such as family, formal education, peers, media, and globalization. Although the family plays an important role as the foundation of character values, formal education and social interaction with schools and peers also make a significant contribution. During rapid technological development, character education strategies must adapt to remain relevant. Parent involvement, the role of teachers as models, and media literacy are important factors in character development